The Impact of Audit Committee Effectiveness on Audit Quality: Evidence from the Middle East - Krayyem Al-Hajaya (International Review of Management and Marketing, 2019)
This study examines the effect of the characteristics of the audit committee, as a tool of corporate governance, on audit quality (as measured by audit fees and type of audit agent) among insurance companies listed on the Amman Stock Exchange (ASE), Jordan. The empirical study was conducted on data of all 23 listed insurance companies for the period of 2013-2017, resulting in 115 observations. Findings of multivariate analyses indicate that companies with larger audit committees and containing a high proportion of non-executive and independent directors are more likely to incur higher audit fees and hire big four audit agents, signalling their prominent level of audit quality. In contrast, more diligent audit committees are more likely to select non-big four auditing firms requiring lower audit fees. The study contributes to the existing body of literature by focusing on the role of the audit committee in enhancing audit quality, especially where there is a lack of such study in emerging economies, especially in the Middle East. The findings of the current study could be useful for regulators and policy makers in the Middle East and Arab region, particularly when they are about to review and set guidelines for effective audit committee characteristics.